2013
DOI: 10.1111/ijn.12215
|View full text |Cite
|
Sign up to set email alerts
|

Family caregivers of adults with acquired physical disability:Thai case–control study

Abstract: This case-control study compares the health of Thai family caregivers of adults with acquired physical disabilities with others without similar responsibilities. To ascertain health perceptions, face-to-face structured interviews using the Short Form (36) were conducted with participants randomly selected from primary care units in eastern Thailand (150 in each group). Despite similar sociodemographic profiles, caregivers reported more health problems and harmful health behaviours. Mean scores for physical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…The functional independence of the person with SCI was an important predictor on QoL of a caregiver with LBP. This result was consistent with previous studies [11,14,24]. In this study, nearly half of the persons with SCI were tetraplegic who were severely impaired and highly-to-totally dependent on their caregivers for daily living activities which may require greater expenditures and more daily caregiving hours.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The functional independence of the person with SCI was an important predictor on QoL of a caregiver with LBP. This result was consistent with previous studies [11,14,24]. In this study, nearly half of the persons with SCI were tetraplegic who were severely impaired and highly-to-totally dependent on their caregivers for daily living activities which may require greater expenditures and more daily caregiving hours.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, caring for persons with SCI with low functional independence is associated with poor QoL of the caregivers. In addition, earlier studies showed that the functional disability of an individual negatively determined their QoL [14,16,17], which is similar to the finding of this present study. Caregivers had chronic LBP resulting from using substantial time and effort in providing physical care for persons with SCI with physical caregiving environment barriers and no caregiver assistant.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, the relationship in Western countries between caregivers and care receivers is not limited to family members and relatives but encompasses a wide range of relationships (Hanyu, ). Thus, culture has a large influence on caregiving behaviours, beliefs, and practices (Lawang, Horey, & Blackford, ), and support for caregivers must accommodate these differences. In Japan specifically, approximately 70% of family caregivers are women, and the trend toward ageing caregivers parallels Japan's increasingly ageing society (Ministry of Health, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Over 95% of all Thai people with disabilities receive care at home and the majority of caregivers are family members. Therefore, their care is solely dependent on family caregivers whose substantial commitment to long-term care can impact significantly on their health [1]. The caregiver caring is also important for long-term care.…”
Section: Introductionmentioning
confidence: 99%